Facile formation of a nanostructured NiP2@C material for advanced lithium-ion battery anode using adsorption property of metal–organic framework. Issue 24 (3rd June 2016) - Li, Gaihua; Yang, Hao; Li, Fengcai; Du, Jia; Shi, Wei; Cheng, Peng
Abstract : Utilizing the adsorption properties of MOFs, a nanostructured NiP2 @C was successfully synthesized, which exhibited enhanced capability for lithium storage in terms of both the reversible specific capacity and high-rate performance. Abstract : Nanostructured NiP2 @C was synthesized by a facile approach via calcination of a Ni-based metal–organic-framework (Ni-MOF-74) with adsorptive red phosphorus, and was tested as an anode material for lithium ion batteries. NiP2 nanoparticles are successfully embedded in situ in porous carbon matrix, constructing crosslinked channels for lithium ion diffusion. The in situ introduction of porous carbon round NiP2 nanoparticles greatly enhances the electronic conductivity. Benefiting from the advantages of porous carbon, the nanostructured NiP2 @C electrode material showed excellent electrochemical performance with high reversibility, high rate capability, and long-term cycling stability.